Glutathione influence on energy metabolism in rat liver mitochondria under experimental nephropathy - Ye. O. Ferenchuk; I. V. Gerush (The Ukrainian Biochemical Journal, 2019)
Mitochondrial oxidative damage and disorders of energy metabolism contribute to a wide range of pathologies and disease progression. In our work, the effect of glutathione on the activity of respiratory chain enzymes and the content of free SH-groups in rat liver mitochondria was examined with the use of folic acid-induced nephropathy model. Mitochondria were isolated by differential centrifugation, NADH-dehydrogenase, succinate dehydrogenase, cytochrome oxidase and H+-ATPase activity were determined. The activity of these enzymes and the content of the free SH-groups in the liver were shown to be decreased under conditions of nephropathy, evidently due to the intensification of the free radical processes. The introduction of glutathione increased the content of SH-groups and the activity of the Complexes II and V enzymes of mitochondrial respiratory chain but did not change the activity of cytochrome oxidase in mitochondria isolated from the liver of rats under experimental nephropathy. The results obtained demonstrate a positive effect of glutathione on mitochondrial succinate dehydrogenase and H+-ATPase activity normalization in the liver of rats with nephropathy. These findings may help to extend the understanding of mitochondrial energy metabolism under development of kidney diseases.